Comparison of recent trends in adolescent and adult cigarette smoking behaviour and brand preferences. (1997) - Cummings, K M; Hyland, A; Pechacek, T F; Orlandi, M; Lynn, W R
Abstract : OBJECTIVE: To compare trends in smoking behaviour and use of cigarette brands by adults and adolescents. DESIGN: Data analysed in this paper come from tobacco use surveys of adults and teenagers conducted in 18 communities in the United States, as part of the National Cancer Institute's Community Intervention Trial for Smoking Cessation. Data on adult smoking behaviour were obtained from two cross-sectional telephone surveys, one conducted from January to May 1988 (n = 99348), and the second conducted between August 1993 and January 1994 (n = 79890). Data on adolescent smoking behaviour were obtained from two school-based surveys of ninth-grade students (aged 13-16 years), one conducted in autumn 1990 (n = 7097), and the second conducted in autumn 1992 (n = 7277). OUTCOME MEASURES: Adult cigarette smoking prevalence was estimated as the percentage of adults (18+ years) who were identified either by interview or by proxy as a current smoker. Among adolescents, current smokers were defined as those who reported having smoked on one or more of the 30 days preceding the interview. Cigarette brand use by adults was measured by asking current smokers to report the six digit UPC code on the side of the pack of their current cigarettes. A master list of UPC code numbers was developed so that reported codes could be associated with specific brand names. Among adolescents, cigarette brand use was measured by asking current smokers who reported that they usually buy their own cigarettes: "What brand do you usually buy?" RESULTS: In ninth-grade students, smoking prevalence rates increased between 1990 and 1992 in 13 of the 18 communities. Among adults, smoking rates declined between 1988 and 1993 in 17 out of 18 communities. Within the same communities, cigarette brand use was found to be much more tightly concentrated in adolescent smokers compared with adults, with teenage smokers more likely to report using the most heavily advertised cigarette brands–Marlboro, Newport, and Camel. CONCLUSIONS: Smoking prevalence rates have increased among teenagers, but have dropped among adults in the same communities. Among adolescents who smoke, and buy their own cigarettes, the three most heavily advertised brands–Marlboro, Camel, and Newport–have a substantially higher market concentration than among adult smokers.